GOVERNMENT REGULATION 46/2013 AS INCOME TAX INCOME FACILITY - Yefni Yefni; Muhammad Habib Gunawan; Suci Nurulita (Universitas Brawijaya, 2017)
Abstract: Government Regulation 46/2013 as Income Tax Income Facility. The purpose of this study is to identify the impact of Government Regulation 46/2013 to the income tax revenue of Micro, Small and Medium Enterprises. This research uses Paired Sample t-Test as data analysis method. This research shows that Government Regulation 46/2013 can be used to increase national income through income tax article 4 (2). This happens because there are easy procedures in the calculation and income tax scheme. Therefore, the researcher recommends that the tax collector's office apply the rules consistently. Abstrak: Peraturan Pemerintah 46/2013 sebagai Sarana Peningkatan Pajak Penghasilan. Tujuan dari penelitian ini adalah mengidentifikasi dampak Peraturan Pemerintah 46/2013 terhadap penerimaan pajak penghasilan Usaha Mikro, Kecil, dan Menengah. Penelitian ini menggunakan Paired Sample t-Test sebagai metode analisis data. Hasil pengujian menunjukkan bahwa Peraturan Pemerintah 46/2013 dapat digunakan untuk meningkatkan pendapatan nasional melalui pajak penghasilan pasal 4 (2). Hal ini terjadi karena terdapat kemudahan prosedur dalam perhitungan dan skema pajak penghasilan. Oleh karena itu, peneliti menyarankan supaya pihak kantor pemungut pajak menerapkan aturan tersebut secara konsisten.